1992
DOI: 10.1093/oxfordjournals.eurheartj.a060251
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal diastolic filling patterns in chronic heart failure—relationship to exercise capacity

Abstract: Abnormal patterns of diastolic ventricular filling are well recognized in chronic heart failure, but their relationship to the severity of heart failure is not known. The present study evaluates the relationship of diastolic filling indices to the severity of heart failure and to exercise capacity. In 40 patients with chronic heart failure secondary to ischaemic left ventricular impairment, exercise capacity was measured as peak oxygen consumption (VO2max) by progressive treadmill exercise. Left ventricular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…This is consistent with recent studies demonstrating that LV diastolic rather than systolic function has an important role in determining exercise performance in patients with CHF. 3,4,25) Many studies have described the contribution of LA function to LV diastolic filling. The LA acts as a reservoir during left ventricular systole, and maintains passive filling during early diastole and active pumping during late diastole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with recent studies demonstrating that LV diastolic rather than systolic function has an important role in determining exercise performance in patients with CHF. 3,4,25) Many studies have described the contribution of LA function to LV diastolic filling. The LA acts as a reservoir during left ventricular systole, and maintains passive filling during early diastole and active pumping during late diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal early "E" and late "A" filling velocities, the E/A ratio, deceleration time of the "E" wave velocity, and IVRT were measured. 4) LA antero-posterior diameters were determined using a parasternal longaxis window. LA systolic diameter (LASd) (maximal LA dimension) was measured at the end of the T wave and LA diastolic diameter (LADd) (minimal LA dimension) was measured at the beginning of the QRS complex on the electrocardiograph.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important reason for this discrepancy is that the functional class is not only associated with left ventricular systolic function, but also with diastolic function [27]. It has previously been demonstrated that diastolic dysfunction is an important determinant of exercise intolerance as well as a predictor of mortality in patients with CHF [28,29]. In our study four of five patients with a normal left ventricular systolic function but with symptoms of CHF, died during follow-up suggesting that diastolic dysfunction may have been a major cause of CHF in these patients.…”
Section: Noninvasive and Invasive Evaluationmentioning
confidence: 99%
“…Controversy exists in the literature regarding the main determinants of heart failure functional class. Some studies have shown that the ability to perform physical exercises is related more to the patterns of diastolic filling of the left ventricle than to the indexes of systolic function [2][3][4] , whereas others have established a direct relationship between functional class and indexes of systolic function 5,6 . The more advanced functional classes (III and IV) are related to greater mortality 1,4,[6][7][8][9][10] .…”
Section: Congestive Heart Failure Correlation Between Functional Clamentioning
confidence: 99%